The World Bank's Assistance for Water Resources Management in China - Varley, Robert C.G. (World Bank, Washington, DC, 2014)
China has an ancient tradition of hydraulic engineering but in the past half century the intensity of exploitation of water resources has accelerated as a result of population and economic growth. The three major issues for Chinese water management are water shortages, flood control and pollution. The World Commission on Dams noted that since 1949 the number of large dams in China had increased from 22 to 22,000, almost half the global total. China has over 80,000 reservoirs and 240,000 km of dikes. Most rivers and streams are now used for irrigation, power generation, transport, urban water supply or waste disposal, some for all of these purposes. The main constraints to integration of Water Resource Management, or WRM arise from the interaction of fairly objective needs for new institutions, incentives and procedures, on the one hand, and bureaucratic interests and political resistance to demand management on the other. China s water problems are not unique, involving a balancing act between economic growth and resource depletion, protection of the environment, health and other non-economic objectives, mediated by strong governments at both central and federal (provincial levels). This paper focuses on the role that the World Bank operations have played in changing WRM policy and strategy during the 1990s.